Salvage high-dose chemotherapy for relapsed pure seminoma in the last 10 years: results from the european Society for Blood and Marrow Transplantation Series 2002-2012 - Necchi, Andrea; Wuchter, Patrick (Clinical genitourinary cancer, 2017)
The optimal management of advanced seminoma that relapses after chemotherapy remains unknown. We retrospectively analyzed outcomes with the use of high-dose chemotherapy (HDCT)